-16=8(7-3t)

Simple and best practice solution for -16=8(7-3t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=8(7-3t) equation:



-16=8(7-3t)
We move all terms to the left:
-16-(8(7-3t))=0
We add all the numbers together, and all the variables
-(8(-3t+7))-16=0
We calculate terms in parentheses: -(8(-3t+7)), so:
8(-3t+7)
We multiply parentheses
-24t+56
Back to the equation:
-(-24t+56)
We get rid of parentheses
24t-56-16=0
We add all the numbers together, and all the variables
24t-72=0
We move all terms containing t to the left, all other terms to the right
24t=72
t=72/24
t=3

See similar equations:

| 9+15x=16x+2 | | x5+15=20 | | 5a=5=7a-19 | | J^2+4j=12 | | 6x+4+80+60=180 | | 26+4y-18=0 | | 3^n-0.1=0 | | u*3=12 | | −6(3x−3)=−90 | | -6+7(8r+1)=7-6r | | 81+x+40+65=180 | | m/8+13=19 | | 2(52+x)=96-10x | | 6(x+15=-102 | | r=–9+r | | 19=4y | | 41=12+7d | | 2x^2+3x=6x+5 | | 8v+7=-41 | | k8+9=21 | | (7x+1)+(5x+3)=136 | | 10x(5.9+)=100 | | 6(2m+30)= | | x+3/15=5/6 | | (3*x-3)=(2*x-1) | | (x+3)/15=5/6 | | 5(m-6)=4m | | 2x-8+4x=34 | | 3x−9=27 | | 14-8x=21 | | 6(5p-8=-168 | | 11=2+3c |

Equations solver categories